An Aromatic Diamine Molecule as the A‐Site Solute for Highly Durable and Efficient Perovskite Solar Cells. Issue 1 (8th November 2018) - Kim, Jinhyun; Hwang, Taehyun; Lee, Byungho; Lee, Sangheon; Park, Kimin; Park, Helen Hejin; Park, Byungwoo
Abstract: Studies of organometallic perovskite solar cells have remarkably progressed within several years, but there still remain concerns of poor stability and insufficient power conversion efficiency (PCE). To overcome these limitations, modification of the perovskite material should be addressed. Herein, imidazole (C3 H4 N2 ) is demonstrated as an A ‐site solute for the conventional methyl‐ammonium lead iodide (CH3 NH3 PbI3 ). As an aromatic hydrocarbon and diamine species with a small ionic radius, imidazole is appropriately alloyed and the bond interactions within the ABX3 lattice are increased. Also, the nature of delocalized π bonding and the unique structure of imidazole allow the formation of an unprecedented kind of hybrid perovskite exhibiting favorable band alignment and optical propertie with high electrical conductivity. Optimal content of imidazole incorporated into CH3 NH3 PbI3 with architectural optimization of the device leads to improved PCEs approaching 20.2% (reverse) with small hysteresis (forward PCE = 19.0%). Furthermore, properly alloyed imidazole into the A ‐site of CH3 NH3 PbI3 leads to extra stability against air, light, and heat. Lastly, devices with a large active area of 2 cm 2 exhibit PCEs as high as 16.8%, further addressing the effect of imidazole on the formation of high quality nanostructured perovskite and devices. Abstract : Imidazole (C3 H4 N2 ) has delocalized π bonding and a diammonium structure, allowing structurally stabilized perovskites with improved electrical properties. Therefore, perovskite solar cells utilized with C3 H4 N2 ‐solued CH3 NH3 PbI3 perform as a highly stable and efficient device. Especially, C3 H4 N2 ‐soluted CH3 NH3 PbI3 exhibit superior stability against heat, light, and humidity. Moreover, (C3 H5 N2 ) x (CH3 NH3 P)1− x PbI3 provides outstanding film quality, allowing high device performance with large active area.